2013
DOI: 10.1111/jop.12089
|View full text |Cite
|
Sign up to set email alerts
|

FasL expression in articular discs of human temporomandibular joint and association with osteoarthrosis

Abstract: A higher area of in situ immunostaining of FasL was found in temporomandibular discs with reduction, which is the less severe condition. Moreover, a reduced expression of FasL in the discs of patients with osteoarthrosis was found, suggesting that some aspects of apoptosis might underlie the progression of TMJ disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For the past few years, many papers have been published showing the participation of various markers and distinct pathways in the progression of TMJ ID using TMJ discs and synovial fluid (Kubota et al, 1998, De Alcantara Camejo et al, 2014, Loreto et al, 2013, Wake et al, 2013, Kim et al, 2012, Leonardi et al, 2010a, Vernal et al, 2008, Sato et al, 2003. Sato et al, in 2003, performed a study using also an immuno-histochemical technique for the examination of synovial tissue from 46 temporomandibular joints with internal derangement in 44 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past few years, many papers have been published showing the participation of various markers and distinct pathways in the progression of TMJ ID using TMJ discs and synovial fluid (Kubota et al, 1998, De Alcantara Camejo et al, 2014, Loreto et al, 2013, Wake et al, 2013, Kim et al, 2012, Leonardi et al, 2010a, Vernal et al, 2008, Sato et al, 2003. Sato et al, in 2003, performed a study using also an immuno-histochemical technique for the examination of synovial tissue from 46 temporomandibular joints with internal derangement in 44 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inflammatory process influences the progression of ID, this study was designed to test the hypothesis that IL-6 may be more highly expressed in the TMJ disc in cases of ADDwR and ADDwoR, and not only in the synovial fluid, as already extensively described in the literature (De Alcantara Camejo et al, 2014, Loreto et al, 2013, Kim et al, 2012, Sato et al, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular joint degenerative disease (TMJ-DD) is a condition that often occurs in women over 40 years of age and is associated with estrogen loss [23]. It has been proven that the fibrocartilage, which covers the articular surfaces, has estrogen receptors responsible for the normal trophism [24,25]. Women with endometriosis are often treated with hormonal therapy to put them into hypoestrogenism, the aim being to suppress their symptoms [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…At this time, it has been speculated that the disc is damaged to varying degrees by excessive mechanical stress, in most cases, becomes deformed, or even perforated. In addition, disc displacement is associated with tissue degeneration, and it is considered to be a risk factor for the occurrence and development of osteoarthritis [4]. It has been shown that dynamic mechanical loading is a crucial stimulus to maintain the homeostasis of TMJ cartilage.…”
Section: Introductionmentioning
confidence: 99%